Synthesis of a 3-hydroxyl-free N-acetyl glucosamine disaccharide - Enugala, Ramu (2020)
A simple and alternative route to a versatile N-acetyl glucosamine disaccharide building block was developed, possessing a free 3-hydroxyl group. In this strategy, the 2,2,2-trichloro-ethoxy carbonyl (Troc) group was used as an amino-and 3-hydroxyl-protecting group.